International Law and Civil Wars : Intervention and Consent. - Lieblich, Eliav (Law, conflict and international relations., 2013)
This book examines the international law of forcible intervention in civil wars, in particular the role of party-consent in affecting the legality of such intervention. In modern international law, it is a near consensus that no state can use force against another - the main exceptions being self-defence and actions mandated by a UN Security Council resolution. However, one more potential exception exists: forcible intervention undertaken upon the invitation or consent of a government, seeking assistance in confronting armed opposition groups within its territory. Although the latter.